Driving Human Granulosa-Luteal Cells Recovered From In Vitro Fertilization Cycles Toward the Follicular Phase Phenotype. (August 2015) - Vireque, Alessandra Aparecida; Campos, Jacira Ribeiro; Dentillo, Daniel Blasioli; Bernuci, Marcelo Picinin; Campos, Carolina Oliveira; Silva-de-Sá, Marcos Felipe; Ferriani, Rui Alberto; Nunes, Altacílio Aparecido; Rosa-e-Silva, Ana Carolina Japur de Sá
Culture systems are available for human granulosa cells (GCs) that perpetuate luteinization. The present study examines the plating density effects and long-term serum-free culture on the in vitro dynamics differentiation of luteinizing human GCs. Cells were cultured in serum-free α-minimum essential medium (α-MEM) or serum-based tissue culture medium (TCM). The time course of GCs morphology and secretion of estradiol (E2), progesterone (P4), and relaxin were analyzed after 48, 96, and 144 hours of culture. Other functional markers as follicle-stimulating hormone/luteinizing hormone receptors and steroidogenic enzymes were investigated at the end of culture. The morphology of an α-MEM cell rather than a TCM cell resembles more closely that seen in vivo. Compared to TCM cultures, α-MEM cells secreted 93.7% and 87.2% more E2 and approximately 7% and 17% of the amount of P4 when cultured at densities of 2 × 10 4 or 4 × 10 4 cells/well, respectively. Relaxin secretion was significantly reduced in α-MEM cultures. α-MEM cells were estrogenic and expressed the CYP19 gene. Levels of CYP17 increased about 8-fold in α-MEM cells above the levels found in TCM cells. Our results reveal new insights into human GCs differentiation in vitro and demonstrate the critical importance of the culture system and cell-plating density on the establishment of estrogenic or progestogenic GC phenotypes.